Signaling in Online Credit Markets - KAWAI, Kei (Institutional Knowledge at Singapore Management University, 2015)
We study how signaling affects equilibrium outcomes and welfare in markets with adverse selection. Using data from an online credit market, we estimate a model of borrowers and lenders where low reserve interest rates can signal low default risk. Comparing a market with and without signaling relative to the benchmark case with no asymmetric information, we find that adverse selection destroys as much as 16% of total surplus, up to 95% of which can be restored with signaling. We also find the credit supply curves to be backward-bending for some markets, consistent with the prediction of Stiglitz and Weiss (1981).